Epistemic justice in public involvement and engagement: Creating conditions for impact - Kristin Liabo; Emma J. Cockcroft; Kate Boddy; Leon Farmer; Silvia Bortoli; Nicky Britten (Wiley, 2022)
Abstract Introduction Patient and public involvement in research is anchored in moral and epistemological rationales. Moral rationales relate to the public having a right to influence how knowledge about them is generated. Epistemological rationales relate to how research design and implementation can improve when informed by experiential, as well as technical, knowledge. In other words, public involvement can increase the epistemological resources of researchers, and contribute to research that is fit for purpose and has high external validity. Methods This article presents an analysis of 3 meetings and 11 interviews with public collaborators and researchers in three UK‐based health research studies. Data comprised transcripts of audio‐recorded research meetings and interviews with public collaborators and researchers. Data were first analysed to develop a data‐informed definition of experiential knowledge, then thematically to investigate how this experiential knowledge was considered and received within the research space. Results At meetings, public collaborators shared their experiential knowledge as stories, comments, questions, answers and when referring to their own roles. They were aware of crossing a boundary from everyday life, and some adapted their contributions to fit within the research space. Although researchers and public collaborators made efforts to create an inclusive climate, obstacles to impact were identified. Conclusions Considering experiential knowledge as a boundary object highlights that this knowledge has a different form to other kinds of knowledge that contribute to research. To enable impact from experiential knowledge, researchers need to create a space where public collaborators experience epistemic justice. Patient and Public Contribution The Peninsula Public Engagement Group (PenPEG) was involved in the planning and conceptualization of the study, including the development of the ethics application and the interview schedules. One member of this group (Richard Fitzgerald) and one from outside the group (Leon Farmer), were full members of the author team and were involved in the data analysis. Leon Farmer has since become a member of PenPEG. Richard Fitzgerald and Leon Farmer were not involved in the three research studies sampled for this study. Sadly Richard Fitzgerald died during the course of this study.